Future-Proofing Islamic Business: A Systematic Review of Strategic Foresight Implementation Using Vosviewer - Anggara, Fajar Surya Ari; Wijaya, Wisnu; Faradisi, Roghiebah Jadwa (IAIN Ponorogo, 2023)
Islamic businesses encounter distinctive problems and opportunities in the current dynamic and uncertain commercial landscape. In VUCA environment, success hinges on the capacity to anticipate future developments and quickly adjust strategies accordingly. What are the current trends, concerns, opportunities, and challenges faced by Islamic businesses while adopting strategic foresight in the VUCA era for future studies? This research’s objective is to identify patterns, problems, prospects, and obstacles encountered by Islamic enterprises in VUCA world. This review seeks to identify essential themes, insights, and patterns regarding trend analysis, concerns, opportunities, and challenges faced by Islamic firms in the VUCA world by a thorough analysis of scholarly works. VOSviewer extracted Scopus search results. We analysed and mapped 590 publications on future-proofing Islamic business: a systematic evaluation of strategic foresight implementation. Based on the mapping results, 200 articles on strategic foresight from 2003 to 2023, 190 about Islamic business terms from 2005 to 2023, and 200 about VUCA from 2013 to 2023 were found. Many potential future research questions related topics such as how can strategic foresight help corporation forecast environmental changes, how can strategic foresight help Islamic business meet changing stakeholders needs, and how can strategic foresight improve Islamic business promising future